Is there any electrophysiological evidence for subliminal error processing? - Shalgi, Shani; Deouell, Leon Y. (Frontiers in Neuroscience, 2013)
The role of error awareness in executive control and modification of behavior is not fully understood. In line with many recent studies showing that awareness is unnecessary for numerous high-level processes such as strategic adjustments and decision making, it was suggested that error detection can also take place unconsciously. The Error Negativity (Ne), long established as a robust error-related component that differentiates between correct responses and errors, was a fine candidate to test this notion: if an Ne is elicited also by errors which are not consciously detected, it would imply a subliminal process involved in error monitoring that does not necessarily lead to awareness of the error. Indeed, for the past decade, the repeated finding of a similar Ne for errors which became aware and errors that did not, compared to the smaller negativity elicited by correct responses, has lent the Ne the prestigious status of an index of subliminal error processing. However, there were several notable execptions. The study in the focus of this review (Shalgi & Deouell, 2012) sheds new light on previous results. We found that error detection as reflected by the Ne is dependent on subjective awareness: when awareness (or lack thereof) is more strictly determined using a wagering paradigm, no Ne is elicited without awareness. This result effectively resolves the issue of why there are many conflicting findings regarding the Ne and error awareness. The average Ne amplitude appears to be influenced by individual criteria for error reporting and therefore studies containing different mixtures of participants who are more confident of their own performance or less confident, or paradigms that either encourage or don’t encourage reporting low confidence errors will show different results. Based on this evidence, it is no longer possible to unquestioningly uphold the notion that the Ne is unrelated to subjective awareness, and that errors are detected without awareness.